INFLUENCE OF AUTOCHTHONOUS SACCHAROMYCES SPP. STRAINS ON THE SULFUR DIOXIDE CONCENTRATION IN WINE - Josip BELJAK; Ana JEROMEL; Stanka HERJAVEC; Sandi ORLIC (Journal of Central European Agriculture, 2008)
The aim of this work was to study the infl uence of 8 autochthonous yeasts strains on the sulfur dioxide formation. For this purpose grape must from the Traminer, Muller Turgau and Chardonnay grapes was used. Yeast strains used were cultivated at the Department for Microbiology, Faculty of Agriculture, University of Zagreb. Five of them were H2S negative and three H2S positive. Tested yeast strains produced from 19 up to 45 mg/l of sulfur dioxide. The highest sulfur dioxide producer was one of the H2S positive yeast strains. The results indicated the initial sugar concentration to be very important for the ratio of sulfur dioxide production. Yeasts were more effi cient at higher sugar levels.